Steel waste used in reducing emissions of nitrous oxide - Batista, Marcelo da Silva; Pereira, Tássia Caroline Passos (Acta Scientiarum. Technology, 2017)
Â Gross wastes of the steel industry were evaluated as catalyst for the reduction of nitrous oxide. The wastes were obtained from steel mill residues (MS), lamination (LA), quenching (QC) and blast furnace powder (BF) and characterized by X-ray fluorescence (XRF), X-ray diffraction (XRD) and hydrogen temperature-programmed reduction (H2-TPR). Results revealed Si, Ca, S, Rh, Fe, Cr, Mn and Cu for all wastes, with iron featuring the greatest amount. H2-TPR analyses showed H2 consumption peaks associated with rhodium oxide, also detected by XRF. The content of comparative rhodium oxide in samples was: MS > LA > QC > BF. N2O conversion increases with increase in temperature for all catalysts. The activity of the catalysts MS > LA > QC > BF was related to rhodium oxide rate in the wastes. Â